2017
DOI: 10.1049/iet-rpg.2016.0089
|View full text |Cite
|
Sign up to set email alerts
|

Slide mode control of microgrid using small hydro driven single‐phase SEIG integrated with solar PV array

Abstract: This study presents a susceptance theory-based sliding mode control (STSMC) algorithm for an improved power quality voltage and frequency control of a single-phase microgrid. The proposed microgrid includes a governor-free small hydro turbine-driven single-phase two winding self-excited induction generator (SEIG), a solar PV array and a battery energy storage system (BESS). The non-linear relationship among magnetising reactance, frequency and speed of SEIG along with random fluctuation in active power output … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 35 publications
0
18
0
8
Order By: Relevance
“…Single-phase induction generators can also be integrated in single-phase microgrids (MG). Such a MG has the load connected across the main winding of a SPIG; an inverterbattery system connected in parallel with the load transfers the power from the other two sources: a permanent magnet synchronous generator (PMSG) -based small wind turbine and a PV panel, both interfaced through power converters with the inverter DC link [71,72].…”
Section: (C)); •mentioning
confidence: 99%
See 2 more Smart Citations
“…Single-phase induction generators can also be integrated in single-phase microgrids (MG). Such a MG has the load connected across the main winding of a SPIG; an inverterbattery system connected in parallel with the load transfers the power from the other two sources: a permanent magnet synchronous generator (PMSG) -based small wind turbine and a PV panel, both interfaced through power converters with the inverter DC link [71,72].…”
Section: (C)); •mentioning
confidence: 99%
“…Another control algorithm, named adaptive sliding mode control, was developed by the authors of [71,72] to ensure, besides voltage and frequency regulation, the SPIG-based MG power quality. It involved two control loops for active and reactive power balancing in case of both sudden load variations and primary resources power modification.…”
Section: Characteristic Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a certain degree of pressure pulsation which cannot be avoided in the draft tube during the operation of a hydropower station [1][2][3]. It can cause turbine output fluctuation, penstock hammer, unit vibration and so on, which brings challenges for the hydro-turbine governing system (HTGS) to regulate the transient characteristics of the hydropower system [4][5][6][7]. In general, draft tube pressure pulsations are often caused by vortex rope in a draft tube under part-load condition.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been reported that PV generation injecting an exceedingly distorted current into the grid [5]. The impacts of the increasing PV generation on the grid has been investigated, and based on the findings of various studies, several control techniques have been developed to reduce the disturbance to the grid, which include sliding mode control [6], Droop control [7], and feedback linearizing control [8]. In each case, these control techniques are integrated with the battery charging/discharging controllers to absorb the PV fluctuation.…”
Section: Introductionmentioning
confidence: 99%